Volume 7: CFD and VIV 2013
DOI: 10.1115/omae2013-10811
|View full text |Cite
|
Sign up to set email alerts
|

Smoothed Particle Hydrodynamics: Benchmarking on Selected Test Cases Within the NextMuSE Initiative

Abstract: In this paper are presented comparisons of SPH variants on academic test cases classically used to validate numerical fluid dynamics software. These comparisons are extracted from NextMuSE FP7 project activities which will be published more extensively in the near future. One of the goals of this project was to better understand the SPH method and to leave the path to its establishment within CFD methods. An important work load was thus dedicated to benchmark SPH variants on selected test cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The velocity profiles along cavity centerlines generated by the present ISPH simulation, employing the same spatial resolution suggested by Le Touzé et al , are shown in Figure . It can be seen that these profiles are in very good agreement with the corresponding results of Ghia et al .…”
Section: Test Casesmentioning
confidence: 83%
See 2 more Smart Citations
“…The velocity profiles along cavity centerlines generated by the present ISPH simulation, employing the same spatial resolution suggested by Le Touzé et al , are shown in Figure . It can be seen that these profiles are in very good agreement with the corresponding results of Ghia et al .…”
Section: Test Casesmentioning
confidence: 83%
“…In this case, a comparison is made with the reference data of Ghia et al only. Le Touzé et al also carried out SPH simulations for this flow regime employing a spatial resolution of L /200. Unfortunately, because of the low quality of the figures in , data for a direct comparison could not be obtained.…”
Section: Test Casesmentioning
confidence: 99%
See 1 more Smart Citation